Mohs micrographic surgery in the elderly: comparison of tumours, surgery and first‐year follow‐up in patients younger and older than 80 years old in REGESMOHS. (5th October 2017) - Camarero‐Mulas, C.; Delgado Jiménez, Y.; Sanmartín‐Jiménez, O.; Garcés, J.R.; Rodríguez‐Prieto, M.A.; Alonso‐Alonso, T.; Miñano Medrano, R.; López‐Estebaranz, J.L.; de Eusebio Murillo, E.; Redondo, P.; Ciudad‐Blanco, C.; Toll‐Abelló, A.; et al.
Abstract: Background: The elderly population is increasing and more patients in this group undergo Mohs micrographic surgery (MMS). The few publications investigating MMS in elderly people conclude that it is a safe procedure; however, these are single‐centre studies without a comparison group. Objective: To compare the characteristics of patients, tumours, MMS and 1‐year follow‐up in patients younger than 80 years, with patients older than 80 years at the time of surgery. Methods: Data was analysed from REGESMOHS, a prospective cohort study of patients treated with MMS. The participating centres were 19 Spanish hospitals where at least one MMS is performed per week. Data on characteristics of the patient, tumour and surgery were recorded. Follow‐up data were collected from two visits; the first within 1 month postsurgery and the second within the first year. Results: From July 2013 to October 2016, 2575 patients that underwent MMS were included in the registry. Of them, 1942 (75.4%) were aged <80 years and 633 (24.6%) were ≥80 years old. In the elderly, the tumour size was significantly higher with a higher proportion of squamous cell carcinoma. Regarding surgery, elderly more commonly had tumours with deeper invasion and required a higher number of Mohs surgery stages, leaving larger defects and requiring more time in the operating room. Despite this, the incidence of postoperative complications was the same in both groups (7%) and there were no significant differences in proportion of relapses in the first‐year follow‐up. Conclusion: The risk of short‐term complications and relapses were similar in elderly and younger groups. MMS is a safe procedure in the elderly.